Aesthetic Limitations in Direct-to-Implant Prepectoral Breast Reconstruction. Issue 1 (2nd May 2022) - Safran, Tyler; Al-Badarin, Faris; Al-Halabi, Becher; Viezel-Mathieu, Alex; Dionisopoulos, Tassos
Abstract : Background: Prepectoral direct-to-implant reconstruction has become an alternative to staged subpectoral expander-based reconstruction. Although the surgical safety of this technique has been shown, aesthetic limitations have not been well-described. This article reports aesthetic limitations and elucidates risk factors that may predispose patients toward developing unfavorable outcomes following direct-to-implant prepectoral breast reconstruction. Methods: A retrospective chart review was performed, identifying patients who underwent prepectoral, direct-to-implant breast reconstruction from June of 2016 to June of 2019. Aesthetic limitations assessed included capsular contracture, rippling, implant malposition, and implant flipping. Results: Two hundred twenty-four consecutive women representing 334 breasts underwent immediate reconstruction performed by a single plastic surgeon. A midlateral incision was used in 185 breasts (55.4 percent) and the Wise pattern in 95 breasts (28.8 percent). The mean follow-up time was 30.5 months (45.3 to 18.3 months). Significant capsular contracture (grade 3 to 4) was noted in 27 breasts (8.1 percent), implant flipping in four breasts (1.2 percent), implant displacement in five breasts (1.5 percent), major rippling in nine breasts (2.7 percent), and minor rippling in 17 breasts (5.1 percent). The use of acellular dermal matrix had no significant effect on the aesthetic outcomes. In comparing breasts with postmastectomy radiation, there was a significant difference in the presence of minor rippling and capsular contracture ( p < 0.05). Conclusions: This cohort represents the largest, single-surgeon, direct-to-implant prepectoral database in the literature. This report shows that aesthetic limitations were comparable to those seen with other forms of reconstruction. Complications did not differ in terms of acellular dermal matrix use. Certain factors can predispose patients to developing unfavorable aesthetic outcomes. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.